Lost in policy translation: Canadian minority Francophones and health disparities - Alimezelli, Hubert Tote; Leis, Anne; Denis, Wilfrid; Karunanayake, Chandima (Canadian Public Policy, 2015)
We reviewed Canadian federal, provincial, and territorial policies related to the health of official language minorities (OLMs) and found important provincial and territorial differences as well as policies penalizing OLMs, which thus contribute significantly to health disparities and to the low vitality of OLM communities. These findings suggest the need for more aggressive, hands-on, and concerted federal and provincial/territorial government efforts to address social inequities and health disparities. Increased policy coherence between these levels of government will not only increase the health and vitality of these populations but also help close the disparity gap and lead to better health and well-being for all Canadians.

La contribution des gouvernements provinciaux et territoriaux à l’épanouissement des communautés francophones en milieu minoritaire Un premier bilan et quelques prospectives - Bourgeois, Daniel; Denis, Wilfrid; Dennie, Donald; Johnson, Marc L. (Institut canadien de recherche sur les minorités liguistiques, 2006)
Depuis près de quarante ans, les gouvernements des neuf provinces et des trois territoires à majorité anglophone œuvrent à promouvoir la langue et la culture françaises en milieu minoritaire, contribuant ainsi à l’épanouissement des communautés francophones. En effet, malgré l’importance de la contribution fédérale, plusieurs secteurs qui relèvent de la compétence exclusive des provinces et des territoires – l’éducation, la santé et les services sociaux et municipaux – contribuent à la vitalité des communautés francophones. L’absence de littérature sur les interventions des provinces et des territoires en matière de langues officielles porterait à croire qu’elles sont rares, voire inexistantes, ou qu’elles visent plutôt à entraver l’épanouissement des communautés francophones. Il n’en est rien. Une compilation et une analyse des interventions provinciales et territoriales dans le domaine des langues officielles étaient donc de mise. Dans un premier temps, il fallait préciser la nature de ces interventions et en produire une compilation systématique. Dans un deuxième temps, il importait d’en dresser un bilan critique. Nous avons par la suite proposé quelques prospectives immédiates et à long terme. Notre recherche porte sur neuf secteurs d’activité : (1) les communications et les services au public en français, (2) la petite enfance, (3) la santé et le bien-être, (4) la justice, (5) les arts et la culture, (6) le développement économique, (7) les groupes cibles (les jeunes, les aînés, les femmes) (8) l’immigration et (9) les municipalités. À la section sur la santé et le bien-être, les thèmes suivants sont abordés: a) Législation et jurisprudence; b) Politique; c) Programmes et services; d) Publications et documentation; e) Appui financier et institutionnalisation; f) Formation professionnelle.
Rapport préparé pour la Conférence ministérielle sur la francophonie

Provincial and Territorial Government Contributions to the Development of Francophone Minority Communities: Assessment and Projections - Bourgeois, Daniel; Denis, Wilfrid; Dennie, Donald; Johnson, Marc L. (Canadian Institute for Research on LInguistic Minorities, 2007)
For more than forty years, the governments of the nine provinces and three northern territories that are majority Anglophone have been striving to promote the language and culture of their Francophone minority and thereby contribute to its development. Indeed, despite the importance of the federal government contribution, sectors such as education, health, and social and municipal services that are areas of exclusive provincial and territorial jurisdiction contribute to the vitality of Francophone communities. The lack of literature on provincial and territorial action in the area of official languages might lead one to think that such action is rare, or even non-existent, or that it is aimed at inhibiting the development of Francophone communities. It is nothing of the sort. Compilation and analysis of provincial and territorial actions in the area of official languages were thus required. It was necessary first to identify the nature of these actions and compile a list of them, and second to assess them critically. We then proposed a few immediate and long-term projections. The research covered nine sectors of activity: 1) public communications and services, 2) early childhood development, 3) health and well-being, 4) justice, 5) arts and culture, 6) economic development, 7) target groups (youth, seniors, and women), 8) immigration and 9) municipalities. The section on Health and Well-being discuss 6 themes: a) Legislation and Case Law; b) Policy; c) Programs and Services; d) Publications and Other Documents; e) Financial Support and Institutionalization; f) Training.
Research report prepared on behalf of the Ministerial Conference on the Canadian Francophonie

Determinants of self-rated health of Francophone seniors in a minority situation in Canada - Alimezelli, Hubert Tote; Leis, Anne; Karunanayake, Chandima; Denis, Wilfrid (Linguistic Minorites and Society, 2013)
Résumé La tendance actuelle montre que les institutions des services de santé et les gouvernements répondent de façon inadéquate aux besoins de plus en plus nombreux d’accès aux services de santé par les populations vieillissantes du Canada et d’autres pays développés. Après l’analyse de l’enquête post-censitaire 2006 de Statistiques Canada sur la Vitalité des Minorités de Langue Officielle, cette étude démontre qu’outre l’age, et en plus d’autres déterminants, les barrières linguistiques auxquelles font face les aînés de langue officielle en situation minoritaire affectent davantage l’autoévaluation de leur santé. Cette étude suggère quelques pistes de solution dont la compréhension des réalités contextuelles, l’amélioration de l’environnement linguistique et des services de santé dans la langue minoritaire. Mots-clés : déterminants de la santé, statut minoritaire, santé perçue, minorités linguistiques, aînés Abstract Current trends show that governments and health institutions in Canada and other developed nations are responding inadequately to the growing need for health services of the increasingly aging population. The Analysis of Statistics Canada’s 2006 post-census Survey on the Vitality of Official Language Minorities show that in addition to age and other socio-demographic determinants, linguistic barriers affect the self-rated health of seniors of official languages living in a minority situation. This study suggests among other things a greater understanding of Official language minorities’ contextual realities, the improvement of both the linguistic environment and services in the minority language. Keywords: health determinants, minority status, self-rated health, linguistic minorities, older adults